Strategies Used in Assessing Mathematics of Teacher Trainees and Effect on the Mathematics Taught in Primary Schools in the South West Region of Cameroon - Forteck Aloysius Betangah (International Journal on Integrated Education, 2021)
This study ‘strategies used in assessing mathematics of teacher trainees and effect on the mathematics taught in primary schools in the South West Region of Cameroon’ was carried out quantitatively with the use of the survey design. All 31 mathematics teacher trainers of teacher training colleges in the South West Region of Cameroon constituted the accessible population. Data was collected with the use of a questionnaire made up of 10 close ended items. Spearman rank correlation was used to analyse the date and the results show that the strategies used in assessing mathematics of teacher trainees have no significant effect on the mathematics taught in primary schools in South West Region. Based on the findings, it is recommended that the coefficient of mathematics in PSTTC could be increased to be among the highest as is the case in primary and secondary schools, mathematics could be assessed in the end of course examination as an independent subject with same high coefficient as general pedagogy, mathematics could be among the subjects to be compulsorily assessed during teaching practice at the end of course examination, and the assessment of student teachers when they teach mathematics during teaching practice could be done solely by mathematics teacher trainers.